Do GnRH Agonists Really Increase Body Weight Gain? Evaluation of a Multicentric Portuguese Cohort of Patients With Central Precocious Puberty - Leite, Ana Luísa; Galo, Elisa; Antunes, Ana; Robalo, Brígida; Amaral, Daniela; Espada, Filipa; Castro, Sofia; Simões Dias, Sara; Limbert, Catarina (Frontiers in Pediatrics, 2022)
Introduction: There are several concerns associated with gonadotropin-releasing hor-mone agonist (GnRHa) treatment for central precocious puberty (CPP), such as obesity and changes in body mass index (BMI). We aimed to investigate whether any anthro-pometric differences exist and if they persist over time. Methods: We conducted an observational study of Portuguese children (both sexes) diagnosed with CPP between January 2000 and December 2017, using a digital plat-form, in order to analyse the influence of GnRHa treatment on BMI-standard deviation score (BMI-SDS). Results: Of the 241 patients diagnosed with CPP, we assessed 92 patients (8% boys) in this study. At baseline, 39% of the patients were overweight. BMI-SDS increased with treatment for girls, but then diminished one year after stopping GnRHa therapy (p=0.018). BMI-SDS variation at the end of treatment was negatively correlated with BMI-SDS at baseline (p<0.001). Boys grew taller and faster during treatment compared to girls (p<0.001) and therefore their BMI-SDS trajectory might be different. Conclusions: This study showed an increase of body weight gain during GnRHa treat-ment only in girls, which reversed just one year after stopping treatment. The overall gain in BMI-SDS with treatment is associated with baseline BMI-SDS.